Artificial intelligence and graduate employability: What should we teach Generation AI? (Journal of Applied Learning and Teaching, 2024)
In the era of Generative Artificial Intelligence (AI), universities are grappling with how best to prepare students for a workforce increasingly influenced by the technology. This commentary explores the implications of AI for graduate employability, emphasising the need for educational institutions to reassess their curricula. It suggests integrating AI literacy and ethical decision-making skills to ensure graduates remain valued by employers. As AI encroaches on graduate-entry and even high-skill jobs, I call for a curriculum that balances technical skills with critical thinking and interpersonal abilities and that prepares students for the complexities of a technology-driven job market.